1965
DOI: 10.1139/m65-105
|View full text |Cite
|
Sign up to set email alerts
|

Sporulation of Bacillus Popilliae on Solid Media

Abstract: Spores of the insect pathogen Bacillus popilliae Dutky have been formed in vitro from vegetative cultures. The procedure results reproducibly in 0.1 to 0.3% spore formation in cells of colonies grown on a solid medium under strictly denned conditions. Sporulation requires a selected strain of the organism, NRRL B-2309S, a relatively large and specific concentration of certain yeast extracts, a specific type of agar, the complete absence of glucose, the presence of acetate, and a pH within the range 7.2 to 7.5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1967
1967
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Sporulation. In vitro production of spores or sporelike bodies by B. popilliae and B. lentimorbus has been reported (5,9,15,16,24,25). Steinkraus and Tashiro (25) and Steinkraus (24) used mainly inocula consisting of spores or vegetative cells (or both) produced in vivo.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Sporulation. In vitro production of spores or sporelike bodies by B. popilliae and B. lentimorbus has been reported (5,9,15,16,24,25). Steinkraus and Tashiro (25) and Steinkraus (24) used mainly inocula consisting of spores or vegetative cells (or both) produced in vivo.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Hrubant, Rhodes, and Hall reported (Bacteriol. Proc., 1965, p. 7) increased sporulation of the same strain and limited sporulation of three other strains by the Rhodes, Roth, and Hrubant (16) method, when it was modified by (among other changes) autoclaving the ingredients separately and by adding a thin, washed agar overlay to the plates before colony development. Haynes and Rhodes (9), using the same strain as Rhodes, Roth, and Hrubant (16), found that it would sporulate in the liquid medium in which it was growing vegetatively, if certain types of activated carbon were added to the medium.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Bacillz~s popilliae Dutky, the causative agent of milky disease in Japanese beetle larvae (Popillia japonica Newman), grows appreciably only under restricted conditions, has limited viability, and sporulates slightly, or not a t all, in laboratory cultures (11,12,15,17,18). Conversely, the organism grows well in larval hemolymph, and spore populations average about 2 X lo9 per larva (1) equivalent t o about 2 X 101° spores per milliliter of larval heinolymph.…”
Section: Introductionmentioning
confidence: 99%
“…Subculturing of the organism during spore production or strain maintenance may introduce the opportunity for the accumulation of genetic changes. Phenotypic variants of NRRL B-2309 have arisen in the past (16,18), and it is possible that previously undetected genetic changes have accumulated in various laboratories.…”
mentioning
confidence: 99%